Open Educational Resources in the Development of Digital Learning Environment - N. V. Dneprovskaya; I. V. Shevtsova (Высшее образование в России)
During the period of the forced transition of universities around the world to the online education, the demand for digital free access services has grown. A unique opportunity has appeared to supplement and develop the theoretical and methodological provisions of online learning based on the analysis of the empirical results that characterize the relevance and effectiveness of the digital environment parts. The educational materials free available at the Internet are the part of the digital environment, which are combined into the concept of open educational resources (OER). The purpose of the study is to assess the relevance of OER for faculty, systematize the main ways of working with them, identify the motives and barriers for the development of OER by faculty. The study conducted among the lecturers at Russian universities showed the high importance and value of OER for their teaching and methodological activities to create and develop the training course content in digital environment. More than half of the faculty staff create and distribute their copyright materials on the Internet on their own initiative for the convenience of their students. The faculty and students freely exchange educational materials using a variety of web services. In conditions of increasing demands on faculty and content of training-course, OER is a valuable resource for educational activities. The analysis of the regulatory framework revealed a lack of OER policy in Russian universities, which is one of the barriers for lecturers to create OER. The results of the study made it possible to develop recommendations for the development of OER in the field of higher education: consolidate the concept of OER in the regulatory framework of education, provide methodological and legal support for the creation and use of OER by faculty, and conduct an information campaign to reveal the prospects and advantages of using OER in higher education.